ANALISA ENGINE PROPELLER MATCHING (EPM) PADA KAPAL RESCUE BOAT KARENA PERUBAHAN TAHAP POWERING PROCESS - Baital, Muhammad Sawal; Putranto, Ari Bawono; Waluyo, Bambang Sri (Gema Teknologi, 2020)
This study is to investigate compatibility between installed main engine in ship with propeller design using theoretical approach and data series. A triple screw rescue boat conducted hard chain hull was used for study and analyze the effect of the changes in powering process stage by observing the result of open water efficiency based on Wageningen Data Series with cavitation analysis has been neglected. The study is considered using intersection between propeller thrust with thrust coefficient and open water efficiency on Wageningen B-Series for fixed pitch propeller. The result indicated that propeller characteristic B5-76 with 41% of efficiencyÂ  has compatibility with specification of installed main engine.